Efficiency and Selectivity Aspects in the C–H Functionalization of Aliphatic Oxygen Heterocycles by Photocatalytic Hydrogen Atom Transfer - Raviola, Carlotta; Ravelli, Davide (Synlett, 2019)
The C–H to C–C conversion in aliphatic oxygen heterocycles (dioxolanes, 1,3-dioxane, or cyclic carbonates) by photocatalytic hydrogen atom transfer and subsequent trapping of the resulting radical with phenyl vinyl sulfone was investigated. The performance of three different photocatalysts, namely tetrabutylammonium decatungstate and the aromatic ketones thioxanthone and 9-fluorenone, was compared. The UV-light-absorbing decatungstate anion is more efficient and permits the use of a smaller excess of hydrogen donor than the aromatic ketones, although the ketones could be excited by visible light. Further intramolecular selectivity studies revealed that aromatic ketones afforded a higher proportion of functionalization at the acetalic versus the ethereal positions than did the decatungstate anion.
Keywords: photocatalysis; hydrogen atom transfer; oxygen heterocycles; chemoselectivity; radicals; C–C bond formation